Social Capital and Human Capital in Supporting Sustainable Aquaculture: The Case of Patuguran Village, Indonesia - Maslia, Anadya Putri; Prayitno, Gunawan; Dinanti, Dian; Suhartini, Wildan; Zahid, Umair; Khan, Rehman Mahmood (Journal of Regional and Rural Studies, 2024)
Patuguran Village is one of the aquaculture center in Pasuruan Regency. Aquaculture that is carried out by the village community is able to improve the local economy. By implementing sustainable aquaculture, the development of aquaculture not only focuses on profit, but also reduces losses and other negative impacts on nature and society. However, the carrying capacity of pond land, availability of fish seeds, limited use of technology, along with limited assistance and training are problems faced by fish farmers in Patuguran Village. Social capital and human capital can be a strategy for aquaculture development by considering the ability of human resources. This study aimed to determine the influence of social capital and human capital in developing sustainable aquaculture in Patuguran Village, Rejoso District, Pasuruan Regency. The data collection method used a questionnaire aimed at 93 respondents and was analyzed with descriptive statistical analysis to identify the characteristics of social capital, human capital, and aquaculture that will be followed by SEM (Structural Equation Modeling). The result showed that the social capital, human capital, and aquaculture is in good condition. There is a positive and significant relationship between social capital and human capital towards sustainable aquaculture.